2000
DOI: 10.1086/315448
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Active Tuberculosis Infection by T Cell Responses to Early‐Secreted Antigenic Target 6‐kDa Protein and Culture Filtrate Protein 10

Abstract: The purified protein derivative (PPD) skin test has no predictive value for tuberculosis (TB) in Mycobacterium bovis bacillus Calmette-Guérin (BCG)-vaccinated individuals because of cross-reactive responses to nonspecific constituents of PPD. T cell responses to early-secreted antigenic target 6-kDa protein (ESAT-6) and the newly identified culture filtrate protein 10 (CFP-10), 2 proteins specifically expressed by M. tuberculosis (MTB) but not by BCG strains, were evaluated. Most TB patients responded to ESAT-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
119
1
6

Year Published

2004
2004
2013
2013

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 187 publications
(139 citation statements)
references
References 18 publications
13
119
1
6
Order By: Relevance
“…The very high specificity of the Rv3879c peptides and the non-cross-reactive sequences of Rv3873, together with their sensitivity of around 50% in culture-confirmed TB patients, identify these peptides as candidates for inclusion in a cocktail of peptides for a T-cell-based diagnostic test. T-cell responses to peptides spanning the lengths of ESAT-6 and CFP10 have been detected in 70 to 80% of TB patients by IFN-␥ ELISA and in around 90% of TB patients by IFN-␥ ELISPOT assay (3,4,6,26,28). We have identified peptides that may further enhance the sensitivity of T-cell-based assays with ESAT-6 and CFP10 without compromising specificity.…”
Section: Vol 72 2004 T-cell Responses To Novel M Tuberculosis Genementioning
confidence: 95%
See 2 more Smart Citations
“…The very high specificity of the Rv3879c peptides and the non-cross-reactive sequences of Rv3873, together with their sensitivity of around 50% in culture-confirmed TB patients, identify these peptides as candidates for inclusion in a cocktail of peptides for a T-cell-based diagnostic test. T-cell responses to peptides spanning the lengths of ESAT-6 and CFP10 have been detected in 70 to 80% of TB patients by IFN-␥ ELISA and in around 90% of TB patients by IFN-␥ ELISPOT assay (3,4,6,26,28). We have identified peptides that may further enhance the sensitivity of T-cell-based assays with ESAT-6 and CFP10 without compromising specificity.…”
Section: Vol 72 2004 T-cell Responses To Novel M Tuberculosis Genementioning
confidence: 95%
“…Two of the low-molecular-mass potent T-cell antigens identified by Andersen and colleagues, early secretory antigen target 6 (ESAT-6) and culture filtrate protein 10 (CFP10), are encoded in RD1 (2, 10) and have been intensively investigated in animal models and humans over the last few years (4,7,15,16,26,30,32,33,36,40). Studies using several different assays, including lymphoproliferation, gamma interferon (IFN-␥) enzyme-linked immunosorbent assay (ELISA), and IFN-␥ enzyme-linked immunospot (ELISPOT) assay, have shown that they are strong targets of the cellular immune response in animal models, TB patients, and contacts (4,11,24,28,30,35,(37)(38)(39).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Both ESAT-6 and CFP-10 have shown great promise as immunodiagnostic reagents for TB in humans and cattle (2,5,39,44). It has been shown that combining M. tuberculosis ESAT-6 and CFP-10 in a diagnostic test for infection or exposure to TB could provide the level of specificity and sensitivity necessary to detect exposure to TB (2).…”
Section: Vol 72 2004 B-and T-cell Epitopes Of Cfp-10 3167mentioning
confidence: 99%
“…In addition immunoreactive orthologs are not expressed in most NTM species (Sorensen et al, 1995;Harboe et al, 1996;Anderson et al, 2000). Several studies have reported that RD1-based (ESAT-6 and/or CFP-10) IFN-γ assays have higher specificity than TST, and are less influenced by previous BCG vaccination (Ravn et al, 1999;Arend et al, 2000;Brock et al, 2001;Mori et al, 2004;Pai et ai., 2004). Newer generation test kits using these two individual antigens have already been developed and reports of their utility are now beginning to emerge (Pai et ai., 2004;Ferrara et al, 2005;Kang et al, 2005).…”
Section: Introductionmentioning
confidence: 99%